Bond Strength of composite repairs using flowable or conventional resins or the association of both - Taciana Marco Ferraz Caneppele; Raira Cruz Calamari; Graziela Ribeiro Batista; Natalia Cortez Gutierrez; Carlos Rocha Gomes Torres (Brazilian Dental Science)
Objectives: The aim of this in vitro study was to evaluate the effects of flowable resin as an intermediate agent on composite repairs on bond strength. Methods: Thirty truncated cones of Grandio SO (VOCO) were prepared and thermo-cycled for 5000 cycles for artificial aging. Specimen’s surface were sandblasted with aluminum oxide, cleaned with air/water spray and conditioned with phosphoric acid for 15s. After that, one coat of Admira Bond Adhesive (VOCO) was applied and light cured for 20s. Specimens were divided into 3 groups according to the repair material used (n= 10): Conventional Resin – Grandio SO (R), A thin layer of Flowable resin – Grandio SO Heavy Flow + conventional Resin (FR) and Flowable resin (F). Over the original specimens, a sectional cone-shape teflon matrix was hold in position , and the cones were built, according the groups described above. Another thirty specimens were built, 10 of each group, simulating a restoration without repair. Specimens were submitted to tensile stress in a universal testing machine. Data were recorded in MPa and evaluated with ANOVA, Tukey´ s and non-paired “t’’ tests. Results: ANOVA showed significant differences between groups which were performed repair (p< 0.00). The results of Tukey´ s test for these groups were: R (19.89 5.31)ab, F+R (14.49 5.59)a, F (20.91 3.99)b. The groups followed by the same letter did not show statistical differences. Non-paired “t” test showed that groups R and F repairs were similar of the correspondent groups which simulated a restoration without repair. Conclusions: The repair with conventional or flowable composite produced bond strength values similar to cohesive strength of the same materials. The use of a thin layer of flowable resin as an intermediate agent in composite repair decreased the bond strength when compared the same method for restoration.